Performance, Emission & Combustion Characteristics of I.C Engine Using Jatropha Methyl Ester Oil and Bio-Diesel Blends (International Journal of Innovative Research in Computer Science & Technology, 2021)
This essay is focused on the idea of  suggesting an alternative fuel for diesel engines. The  experiments show that the diesel-biodiesel blends can be  used as substitute fuels for diesel engines. Recent studies  have demonstrated that the use of diesel biodiesel blends  can significantly lower emissions of carbon monoxide  (CO), total hydrocarbons (HC), and particulate matter. The mixing of biodiesel with diesel significantly reduces the emission particulate matter (PM) because the blended biodiesel contains oxygen. It was recommended that some  alternative fuels that are climate-friendly based on various  experiments. There for in the present study these lected  biodiesel is jatropha seed oil which was obtained by Trans esterification process by crude seed oil, because the large  availability and easily extract from seed by different  process.
Keywords: Biodiesel; Bio fuels; Blending Jatropha; Renewable energy; CO; HC; PM and Trans-esterification etc